Redução da vogal [u] adjacente á vogal alta anterior: Uma investigação sobre a implementação da redução vocálica - Cecilia Valle Souza Toledo (2019)
This dissertation aims at analysing vowel reduction in (high front vowel + high back vowel) sequences in the Belo Horizonte variety of Brazilian Portuguese, e.g. [i]~[i] tio, [ma]~[ma] maio, [lab] ~[lab] lábio. We intended to characterise the vowel reduction implementation through an experimental analysis. The adopted theoretical assumptions are the Exemplar Theory (BYBEE, 2001, 2002; PIERREHUMBERT, 2001, 2003; JOHNSON, 2007) and the Laboratory Phonology (PIERREHUMBERT, BECKMANN e LADD, 2000). The corpus was composed of recordings of readings produced by 10 native informants from Belo Horizonte, aged from 18 to 29 years old. The words in the corpus are 964 nouns and verbs which presents the final sequence (high front vowel + unstressed final []). Both nouns and verbs were selected in order to test if there is grammatical conditioning in the vowel reduction trajectory. Results indicate that vowel reduction is a gradient phenomenon: the high front vowel followed by the reduced [] is lengthened and centralised in the vowel reduction context. We suggest that the lengthening and the centralisation of the high front vowel adjacent to the reduced [] express the relevance of phonetic detail to the comprehension of vowel reduction. Moreover, results suggest that verbs and nouns do not present significantly different indices of vowel reduction, i.e., it is not possible to claim that vowel reduction is grammatically conditioned. On the other hand, the lexical item and the individual proved to be relevant factors in the understanding of the reduction trajectory. Different words presented different levels of vowel reduction. This result corroborates claims from the Exemplar Theory that consider that language change implementation is lexically gradual. Each individual presented a specific behaviour towards the vowel reduction. Individual particularities corroborate claims from the Exemplar Theory that consider that individual language experience is relevant to the comprehension of phonological representation.